Retropharyngeal effusion in acute calcific prevertebral tendinitis: diagnosis with CT and MR imaging. - Eastwood, J D; Hudgins, P A; Malone, D (American Journal of Neuroradiology, 1998)
Three patients with the diagnosis of acute calcific prevertebral tendinitis underwent CT or a combination of CT and MR imaging, which showed previously described findings of calcifications within the tendons of the longus colli muscles. In addition, however, we detected a retropharyngeal effusion in all three patients. The importance of this finding lies in the need to differentiate this effusion from retropharyngeal infection.